Predictors and significance of histologic response to neoadjuvant therapy for gastric cancer. Issue 8 (18th March 2021) - Rajabnejad, Ataollah; Vaida, Florin; Valasek, Mark; Razzaque, Saqib; Fanta, Paul; Horgan, Santiago; Bouvet, Michael; Lowy, Andrew M.; Kelly, Kaitlyn J.
Abstract: Background: Perioperative therapy is the standard‐of‐care for locally‐advanced gastric cancer but many patients do not respond. There are currently no known factors that predict response to therapy. Methods: This was a retrospective study aimed to evaluate treatment effect grade (TEG) in patients with locally advanced gastric cancer treated with neoadjuvant therapy and surgery at a single center. Ordinal logistic regression was performed to identify predictors of TEG, scaled from 0 to 3. Results: Fifty patients were identified. The majority were male ( n  = 33) and 50% were Hispanic. The most common regimens given were: 5‐fluorouracil/leucovorin, oxaliplatin, and docetaxel ( n  = 23, 46%), epirubicin, cis‐ or oxaliplatin, and 5‐fluorouracil/leucovorin or Xeloda ( n  = 8, 16%), and 5‐fluorouracil/leucovorin and oxaliplatin ( n  = 9, 18%). Twenty‐seven patients (55%) had complete or partial response to therapy (TEG 0–2), and 23 patients (46%) had no response (TEG 3). Of numerous variables analyzed, only race and SRC histology were associated with TEG. TEG was associated with disease free, but not disease specific survival. Conclusions: In this cohort, 46% of patients had no histologic response to therapy. SRC histology, and possibly race, should be considered in determination of optimal multidisciplinary regimens and in amount of therapy to be given upfront, as patients with SRC histology and those of non‐Asian race are less likely to respond to standard regimens.